Investigations into the clinical and immunological components as well as virus – induced modulation of the endothelium in dengue / Anusyah Rathakrishnan - Rathakrishnan, Anusyah (2014)
Dengue is one of most widespread vector-borne disease throughout the world. Even with vector control programs, the fight against dengue has been tough with many endemic countries suffering from serious healthcare, economic and social burden. The pathogenesis of dengue remains elusive and complicated with a complex interplay between the virus, mosquito and host immune system. This study sought to investigate host-mediated immunopathogenesis in a Malaysian dengue cohort and dengue virus mediated endothelial dysfunction. Recruitment of dengue suspected patients was conducted in Ampang Hospital and Tengku Ampuan Rahimah Hospital in 2010-2011. Patients were classified as non-dengue (9.3%), dengue without warning signs (12.7%), dengue with warning signs (77.0%) and severe dengue (1.0%). Clinically, thrombocytopenia, increased vWF and prolonged clotting time serve as good markers for disease progression but not as a differentiator for patients with and without warning signs. The elevated levels of liver enzymes, ALT and AST, are also good indicator for dengue disease progression. Diagnosis based solely on clinical symptoms and parameter is insufficient, but IgM laboratory diagnosis alone is also inappropriate. Using multiple diagnostics assays, 37% were misdiagnosed as non-dengue and 23% of the clinically classified dengue patients were found to be negative for all tests. HLA-A*24 and -B*57 were positively associated with Chinese and Indians patients with warning signs, respectively, whereas A*03 may be protective in the Malays. HLA-A*33 was also positively associated in patients with warning signs. Dengue NS1, NS2A, NS4A and NS4B were found to be important T cell epitopes; however with no apparent difference between with and without warning signs patients. Distinction between the 2 groups of patients was also not observed in any of the cytokines analyzed; nevertheless, 12 were significantly differentially expressed at the different phases of illness namely IL-5, IL-10, IL-13, IFN-γ, MIF, IL-8, CCL11, CXCL10, IL-7, FGF-2, ICAM-1 and VCAM-1. The elevated levels of adhesion molecules often imply endothelial activation and therefore, the interaction between DENV and endothelial cells was studied in vitro. In this study, the brain and lung microvascular endothelial cells were found to be susceptible to dengue virus infections. Real time monitoring of DENV-infected brain and lung endothelium barrier resistance showed an immediate response upon infection which indicates that the barriers was disrupted. In the brain ECs, after 24 hours, the barrier of infected cells were tighter than the non-infected while in the lung, the barrier remained disrupted up to 72 hours. Protein expression studies corroborated with this finding where the tight junction proteins were modulated differentially. Investigations into the oxidative stress markers upon infection also showed differential expression in the levels of total nitric oxide, reactive oxygen species and endothelial nitric oxide synthase. These markers not only differed by time but also were expressed contradistinctively in the 2 different cell lines tested. This may be explained by the functional heterogeneity in microvascular endothelial cells from different organs. In conclusion, this is the first study to describe the clinical and immunological profile of dengue patients in Malaysia based-on the revised dengue classification. The dengue-HLA associations, dengue patients T cell responses and cytokine profiling provide valuable information for development of vaccines, drugs, adjuvants and anti-cytokine therapies. In this study activation of the endothelial cells seemed to have occurred immediately upon dengue infection and is regulated differentially in different organs. This is postulated to trigger the various cascades of immune response as noted in dengue patients. As endothelium dysfunctions are often reversible, this may provide avenues for development potential pharmacologic agents to manage disease severity.